The association between ultra-processed food consumption and health-related quality of life differs across lifestyle and socioeconomic strata - Somayeh Hosseinpour-Niazi; Mahdieh Niknam; Parisa Amiri; Parvin Mirmiran; Elaheh Ainy; Neda Izadi; Zahra Gaeini; Fereidoun Azizi (BMC, 2024)
Abstract Background In this prospective study, we aimed to examine the association between ultra-processed foods and health-related quality of life (HRQoL) and to evaluate the effect of lifestyle and socioeconomic factors on this association. Methods This study included 1766 adults (aged 18 to 78, 54.3% women), who took part in the Tehran Lipid and Glucose study. The Short-Form 12-Item Health Survey version 2 was used to determine HRQoL, which includes the physical component summary (PCS) and mental component summary (MCS) scores. Ultra-processed food consumption was assessed using a validated semi-quantitative food frequency questionnaire. Lifestyle (physical activity and smoking status) and socioeconomic factors (education level and employment status) were also determined. General linear models (GLM) were applied to estimate the mean (95% confidence interval) for MCS and PCS scores across the ultra-processed foods tertiles. Additionally, the effect of lifestyle and socioeconomic factors on the relationship between ultra-processed foods and HRQoL was examined using GLM. Results The median consumption of ultra-processed foods was 11.9% (IQR: 8.2 to 16.8) of total energy intake. There was a significant inverse association between ultra-processed foods consumption and PCS, but not MCS, after adjustment for confounding factors. Significant interactions were observed between ultra-processed food consumption, sex, and occupation on PCS score (all P values < 0.001). The interaction test tended to be significant for smoking status, education levels, and physical activity levels. As ultra-processed food consumption increased, the PCS score significantly decreased in women (P = 0.043), low physical active subjects (P = 0.014), smokers (P = 0.015), and lower-educated individuals (P = 0.022). Non-employed individuals with higher ultra-processed food intake showed a decline in their PCS and MCS scores. While there was no significant difference in MCS score among different strata of lifestyle and socioeconomic status across tertiles of ultra-processed foods. Conclusions Higher intake of ultra-processed foods was associated with poorer physical health, particularly among women, those with unhealthy lifestyles, and low socioeconomic conditions.